Real, Realistic Ring Waves for Surge Testing - Martzloff, Francois D.; Pellegrini, Giuseppe (9th International Zurich Symposium and Technical Exhibition on Electromagnetic Compatibility, 1991)
Five independent investigations on the coupling of surges into low-voltage circuits (data or power lines), and of their effects, show that a damped oscillatory transient is a real, realistic stress for equipment connected to these lines.